Fast or slow: An evaluation of Ti-in-quartz diffusion coefficients through comparisons of quartz and plagioclase diffusion times - Wang, Sophia Y.; Gualda, Guilherme A. R.; Lubbers, Jordan; Kent, Adam J. R. (Volcanica, 2025)
Diffusion geochronometry using Ti-in-quartz has become a valuable method in understanding the evolution of silicic magmas. However, four different options for Ti diffusivity (DTi) currently exist, spanning three orders of magnitude, resulting in substantially different estimated times and interpretations. We present Ti-in-quartz diffusion times for the Cerro Galán Ignimbrite using the Cherniak et al. [2007] (10.1016/j.chemgeo.2006.09.001), Audétat et al. [2021] (10.1130/g48785.1), Audétat et al. [2023] (10.1038/s41467-023-39912-5), and Jollands et al. [2020] (10.1130/g47238.1) DTi value and (1) compare these against plagioclase diffusion times derived from the same samples, (2) consider evidence for Ti diffusion in quartz under relevant magmatic timescales, and (3) compute derived quartz growth rates for crystals from the Cerro Galán Ignimbrite. On all accounts, we find that the Cherniak et al. [2007] diffusion coefficient yields diffusion times that agree much better with independent evidence than those derived using slower DTi values [Jollands et al. 2020; Audétat et al. 2021; 2023].